Faktor-faktor yang Mempengaruhi Pembelian Daging Ayam di Pasar Inpres Kota Padang Sidimpuan Selama Pandemi Covid-19 - Ali Hardana; Risna Hairani Sitompul; Desy Khairani (Studi Ekonomi dan Kebijakan Publik, 2023)
Purpose: This research study aims to find out the factors of buying chicken meat in traditional markets during the Covid-19 pandemic. This research was conducted in Inpres Market, Inpres Sub district, Padangsidimpuan City, Province of West Java on November 7 to December 12, 2021. Methodology: The sampling method used is purposive sampling, using 104 respondents. The results showed the characteristics of consumers who buy chicken meat in Inpres Market on average women, over 36 years of age, high school education/equivalent, housewife work, income below IDR.1,000,000.00, consumption rate of 1-1.5 Kg in a week and purchase rate as much as 1-3 times a week. Result: The results of the multiple linear regression equations obtained a coefficient of determination of 0.727 which indicates that the health protocols (X1), marketing mix (X2) needs (X3) and purchase intention (X4) affect purchasing decisions (Y) by 62.8%. The F test concluded that health protocols, marketing mix, needs and purchase intention had a significant influence on purchasing decisions. The T test concluded that health protocols, marketing mix, needs, and interests significantly influenced purchasing decisions. Therefore, the advice given according to the results is with chicken traders in Inpres Market, among others, traders must always adhere to health protocols in serving consumers, maintaining the cleanliness of outlets and providing services by considering selling using the method of delivery or online, in order to reduce crowds in the market where the market is one of the places that is indeed a lot of spread of the Covid-19 virus.